A tunable optical add-drop multiplexer - Craciun, Viorel (University of Ottawa (Canada), 2003)
Tunable add-drop multiplexer systems that are feasible and exhibit good performance characteristics are highly desirable for building all-optical transmission systems. A novel sparse tunable optical add/drop multiplexer subsystem consisting of eight tunable single-ring resonator based optical filters, and two eight-channel phase array devices, is proposed to allow sparse optical channels add and/or drop. The design takes advantage of the main limitation of single ring resonator-based optical filters, namely the rather limited free spectral range and in effect the limited number of communication channels that can be processed. The tunable filters provide add and drop functions of the selected channels whereas the phase array devices provide demultiplexing and multiplexing functions for the inbound and the outbound channels respectively. The coupled mode theory, its transfer matrix formalism, and the theory of spectral analysis of signals are used to carry out preliminary performance analysis of the single-ring resonator based tunable add-drop filter, to optimize, and finally to characterize its performance. This approach allows an accurate evaluation of filter characteristics, namely the transfer functions between any ports of the device. A wavelength-domain simulation method, coupled with a time/frequency-domain simulation method, is used to analyse the performance of the tunable OADM in linear, ring, and mesh all-optical wavelength-division multiplexing networks/transmission systems. Our performance evaluation demonstrates that the tunable OADM could be successfully employed in linear, ring, and mesh all-optical dense-division multiplexing networks/transmission systems with bit rates up to 10 Gbit/s.
Keywords: Engineering, Electronics and Electrical.